A review of solar energy driven desalination technologies. (January 2015) - Sharon, H.; Reddy, K.S.
Abstract: Water plays an important role in all our day to day activities and its consumption is increasing day by day because of increased living standards of mankind. Some regions of the globe are under severe stress due to water scarcity and pollution. The fresh water needs of mankind can be only satisfied if saline water which is available in plenty is converted to potable water by desalination. Desalination industry has shown increased threats of CO2 emissions and severe environmental impacts. Desalination industry can be made sustainable if they are integrated with renewable energy and if proper brine disposal methods are followed. In this review different desalination units integrated with renewable energy with special emphasis given to solar energy is discussed. The problems associated with desalination units and their remedies have been presented. Apart from this some novel methods of desalination process has also been explained. This review will allow the researchers to choose appropriate desalination technology for further development.